The Long Shadow of Short-Term Schooling Disruption : Analysis of Kuwait's Civil Service Payroll Data - Bilo, Simon; Ajwad, Mohamed Ihsan; Alansari, Ebtesam; Alhumaidan, Lama; AlRashidi, Faleh (World Bank, Washington, DC, 2021)
This paper estimates the long-term impacts of schooling disruptions on private returns to schooling in Kuwait. It applies an instrumental variables approach to estimate the private returns to schooling, using unique civil service payroll data, with Kuwaiti students’ exposure to the Gulf War (1990–91) as the instrument. The Gulf War is a suitable instrument because it profoundly affected Kuwaiti students' schooling at the time and is unlikely to be correlated with many potentially problematic omitted variables, such as students’ ability. The analysis finds that (i) people who were of schooling age during the Gulf War tend to have lower educational attainment than people who were of schooling age after the Gulf War; (ii) men who were of schooling age at the time of the Gulf War earn on average 5.6 percent less for each year of schooling lost, and women earn correspondingly 6.8 percent less for each year of schooling lost; (iii) students who were in lower grades during the Gulf War tend to suffer a greater percentage wage loss for each year of lost schooling.